2016
DOI: 10.1016/j.culher.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Framing the past: How virtual experience affects bodily description of artefacts

Abstract: a b s t r a c tThis study uses a novel, interdisciplinary approach to investigate how people describe ancient artefacts. Here, we focus on gestures. Researchers have shown that gestures are important in communication, and those researchers often make a distinction between beat and iconic gestures. Iconic gestures convey meaning, specifically, visual-spatial information. Beat gestures do not convey meaning; they facilitate lexical access. In our study, we videotaped participants while they described artefacts p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Technologies for virtuality are another privileged resource for the museums' digital transition due to their immediate and evident appeal and attractiveness, receiving a wide response from institutions above all for purposes related to increased visit flow. A whole vein of explorative research studies, actually, has been developed on the potentialities of those technologies and their role in museum communication, especially in the reconstruction of objects, people, and complete environments [45][46][47], mainly for on-site use to enrich the visit experience and add precious informative content about objects, their original context and use, or generally, their stories [48], up to hypothesizing and applying the concept of a virtual museum in its complex [49,50]. From this point of view, the perceived potential of this concept has led to meditations above all on definitions and possible classifications with respect to different levels of complexity and interactivity [6,51,52], although the first efforts to apply the concept date back several years [53].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Technologies for virtuality are another privileged resource for the museums' digital transition due to their immediate and evident appeal and attractiveness, receiving a wide response from institutions above all for purposes related to increased visit flow. A whole vein of explorative research studies, actually, has been developed on the potentialities of those technologies and their role in museum communication, especially in the reconstruction of objects, people, and complete environments [45][46][47], mainly for on-site use to enrich the visit experience and add precious informative content about objects, their original context and use, or generally, their stories [48], up to hypothesizing and applying the concept of a virtual museum in its complex [49,50]. From this point of view, the perceived potential of this concept has led to meditations above all on definitions and possible classifications with respect to different levels of complexity and interactivity [6,51,52], although the first efforts to apply the concept date back several years [53].…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, experimental studies and studies of proofs-of-concept have primarily addressed issues similar to those discussed in the context of traditional replicas; for example, how handling and manipulation of 3D printouts affect our perceptive experiences in relation to conventional ways of seeing objects in a display case, on a computer monitor, or by using stereoscopic and haptic devices (see e.g. Di Giuseppantonio Di Franco et al 2015; 2016; Williams 2017). Although 3D printing is still at its early stages, especially in heritage contexts, theorization has started moving beyond the concept of replica making, addressing the key question of authenticity (Jones et al 2017) and posing grand challenges for archaeological practice, including the rematerialization of archaeological features unearthed in the field (Beale & Reilly 2017; see also Reilly et al 2016).…”
Section: Towards Sensorial Digital Archaeologiesmentioning
confidence: 99%
“…Studies and experiments involving the use of immersive, multisensory virtual reality, 3D-printed objects, and haptic interactions through virtual or augmented reality have demonstrated that these have an effect on how the past and ancient artefacts are experienced by people, therefore establishing them as a potentially fruitful venue for experimenting with the post-human and the past (Di Giuseppantonio Di Franco et al, 2015, 2016; Eve, 2017, 2018). Here, I argue that a possible entry lies in incorporating virtuality more broadly and using the affective agency of digital methods to create post-human environments and non-anthropocentric perceptions (see Figure 4).…”
Section: Towards a Post-humanist Framework In Roman Heritage: Not Feementioning
confidence: 99%